Монгол хэлний ойролцоо утга бүхий хоршоо үгс хэлц цогцолбор бүтээх тухайд - Б.Мөнгөнцэцэг, (Acta Mongolica, 2013)
Based on the relation which big units language includes the small ones while bigger parts includes smaller, we tried to show the synonymous phrasal expression how can be compared with the synonym phrases as the intermediate unit. Mongolian mind can express and it's features in them. Synonyms make compound nouns when their meaning is similar or same, but when it has become different according to their meaning make phrasal expressions which ha\ e the parallel meaning and type. To clarify, we can say that Mongolian phrasal expression is originated from the byword which has the similar meaning. Providing synonymous bywords phonetic and meaning used heading and ending combined, lines are equalized, passed the lines and parallelized to each lines separately.